AI-Powered Tools and Their Role in Developing Speaking Fluency in EFL Contexts - Ilma Sania Ramadhani (Yayasan Insan Cipta Medan, 2025)
Speaking fluency remains a major challenge for learners of English as a Foreign Language (EFL), particularly in contexts where opportunities for authentic oral interaction are limited. Recent developments in artificial intelligence (AI) offer new possibilities for enhancing speaking instruction through personalized, interactive, and low-anxiety learning environments. This study investigates the integration of AI-powered tools to enhance speaking fluency in EFL classrooms. Employing a qualitative descriptive research design, the study was conducted in an EFL classroom where speech recognition applications, AI-based chatbots, and automated feedback platforms were integrated into regular speaking activities over one academic term. Data were collected through classroom observations, speaking performance tasks, and semi-structured interviews. The findings reveal that AI-powered tools contributed to improvements in students’ speaking fluency, as reflected in increased speech continuity, reduced hesitation, and greater confidence in oral communication. Additionally, students expressed positive perceptions of AI-assisted speaking practice, highlighting increased motivation, reduced anxiety, and enhanced learner autonomy. The study concludes that AI-powered tools can serve as effective complementary resources in EFL speaking instruction when supported by appropriate pedagogical guidance. The findings provide practical implications for EFL teachers and contribute to the growing body of research on AI-assisted language learning.